The Effect Of Supervision On Employee Performance At The South Binjai Sub-District Office - Yodi Putama Sika; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2024)
This study aimed to examine the effect of supervision on employee performance at the Binjai Selatan Subdistrict Office. The study used a quantitative method with a simple linear regression approach to analyze the relationship between supervision as the independent variable and employee performance as the dependent variable. Data were collected through questionnaires distributed to employees at the Binjai Selatan Subdistrict Office, with a total of 117 respondents. The results showed that supervision had a positive and significant effect on employee performance, with a regression coefficient of 1.201, indicating that every 1-point increase in supervision would improve employee performance by 1.201 points. The t-test showed a t-value of 13.416 > t-table value of 1.67866, with a significance value of 0.000, meaning the alternative hypothesis was accepted and the null hypothesis was rejected. The coefficient of determination analysis resulted in an Adjusted R Square value of 0.591, indicating that supervision could explain 59.1% of the variability in employee performance. These findings suggested that good supervision could improve employee performance in the organization, although other factors not examined in this study also influenced employee performance. This study provides important contributions to human resource management, particularly in efforts to improve employee performance through effective and efficient supervision.